Conceptual issues in the role of education decentralization in promoting effective schooling in Asian Developing countries September 2002 Jere R. Behrman, Anil B. Deolalikar, Lee-Ying Soon - BEHRMAN, Jere R; Dealalikar, Anil B; Soon, Lee-Ying (Asian Development Bank, 2002)
ix, 51 hlm 28 cm